Tep1 Regulates Yki Activity in Neural Stem Cells in Drosophila Glioma Model - Gangwani, Karishma; Snigdha, Kirti; Kango-Singh, Madhuri (Frontiers in Cell and Developmental Biology, 2020)
Glioblastoma Multiforme (GBM) is the most common form of malignant brain tumor with poor prognosis. Amplification of Epidermal Growth Factor Receptor (EGFR), and mutations leading to activation of Phosphatidyl-Inositol-3 Kinase (PI3K) pathway are commonly associated with GBM. Using a previously published Drosophila glioma model generated by coactivation of PI3K and EGFR pathways [by downregulation of Pten and overexpression of oncogenic Ras] in glial cells, we showed that the Drosophila Tep1 gene (ortholog of human CD109) regulates Yki (the Drosophila ortholog of human YAP/TAZ) via an evolutionarily conserved mechanism. Oncogenic signaling by the YAP/TAZ pathway occurs in cells that acquire CD109 expression in response to the inflammatory environment induced by radiation in clinically relevant models. Further, downregulation of Tep1 caused a reduction in Yki activity and reduced glioma growth. A key function of Yki in larval CNS is stem cell renewal and formation of neuroblasts. Other reports suggest different upstream regulators of Yki activity in the optic lobe versus the central brain regions of the larval CNS. We hypothesized that Tep1 interacts with the Hippo pathway effector Yki to regulate neuroblast numbers. We tested if Tep1 acts through Yki to affect glioma growth, and if in normal cells Tep1 affects neuroblast number and proliferation. Our data suggests that Tep1 affects Yki mediated stem cell renewal in glioma, as reduction of Tep significantly decreases the number of neuroblasts in glioma. Thus, we identify Tep1-Yki interaction in the larval CNS that plays a key role in glioma growth and progression.